Impact of Sharia Kur financing on performance of MSMEs financing of Indoensian Syariah Banking - Hsb, Sarmania; Syahbudi, Muhammad; Yanti, Nursantri (Journal La Sociale, 2024)
Financing for Micro, Small and Medium Enterprises (UMKM) has an important role in the local economy, especially in rural areas such as Gunung Tua, North Padang Lawas. Bank Syariah Indonesia (BSI) Gunung Tua Sub-Branch Office (KCP) provides Sharia People's Business Credit (KUR) financing to support MSMEs in increasing working capital and investment. This research aims to examine the impact of KUR Syariah financing on the Performing Financing of UMKM under the guidance of BSI KCP Gunung Tua. The research method used is mix method with a case study approach. Data was collected through in-depth interviews with KUR Syariah BSI KCP Gunung Tua managers and UMKM owners who received financing, as well as through direct observation and analysis of related documents. The research results show that KUR Syariah financing from BSI KCP Gunung Tua has a positive impact on increasing UMKM Financing Performance. The socialization and information dissemination strategy carried out by BSI KCP Gunung Tua has succeeded in increasing UMKM awareness and interest in KUR Syariah financing. An easy and transparent financing process and the implementation of a strict monitoring system also support the effectiveness of this financing. KUR Syariah financing from BSI KCP Gunung Tua not only provides the capital needed by UMKM, but also plays an important role in the economic empowerment of UMKM and local communities. By continuing to improve marketing and service strategies, BSI can continue to be a reliable partner for UMKM in developing their businesses.